Índice de estética dental (DAI) y necesidad de tratamiento ortodóntico en los estudiantes que cursan el Primer Año de la Facultad de Salud Humana de la Universidad Nacional de Loja 2018 - 2019 - Maldonado Aguilar, Mariuxi del Cisne (2019)
The Dental Aesthetics Index (DAI) explores the aesthetic part of occlusion and relates them to clinical components mathematically to obtain a numerical value that corresponds to a category of malocclusion and determines the need for orthodontic treatment. Objective: to determine the need for orthodontic treatment by using the Dental Aesthetics Index (DAI) in students in the first year of the Faculty of Human Health of Universidad Nacional de Loja. Methods: This is an observational, descriptive and cross sectional epidemiological study that was conducted in a sample of 60 orthodontic pretreatment study models where the respective 10 parameters of the DAI index were analyzed and measured. Results: 66.67% have a degree of malocclusion and require some form of orthodontic treatment, being distributed as follows: defined malocclusion with effective treatment (28.30%), severe malocclusion with highly desirable treatment patient (21.70%) and very severe malocclusion with mandatory and priority treatment (16.70%); in turn the remaining 33.33% do not have the need for treatment or if established this is less since they have normal occlusion or minimal malocclusion. Conclusion: most of the study population has some of the types of malocclusion and their corresponding need for orthodontic treatment determined by the DAI index, in the male sex there is a higher rate of malocclusion of the type very severe; according to age, the rank of the greatest occlusion problems is those aged nineteen and up. Keywords: Dental Aesthetics Index (DAI), need for orthodontic treatment; malocclusion.